A Novel Solution to the Cognitive Radio Decision Engine Based on Improved Multi-Objective Artificial Bee Colony Algorithm and Fuzzy Reasoning. Issue 4 (2nd October 2017) - You, Xiaojian; He, Xiaohai; Han, Xuemei
Abstract: Targeting at the parameters reconfiguration of a cognitive radio system, a novel cognitive decision engine (CDE), based on an improved multi-objective artificial bee colony (IMOABC) algorithm and fuzzy reasoning, is proposed. First, a group of Pareto optimal solutions were obtained by applying IMOABC to solve CDE, and an optimal solution that meets user needs was selected by fuzzy reasoning. Such IMOABC algorithm was integrated into society cognitive strategies. New production and preservation mechanisms of individuals and parallel hybrid coding and multi-dimensional evolution strategies are evaluated. The proposed algorithm was evaluated on a set of standard test functions. Combined with the multi-carrier communication system, the simulation experiments are performed for reconfiguring of the physical layer parameters, and the results are able to satisfy user needs.